Mechanical properties of stabilized soils for pavement applications - Feng, Mingwei (2020)
With the continuous development of economy and society, the requirement of road pavement construction is increasing gradually in China. The mining of traditional road fill materials such as sand, stone causes a lot of wastes, which has a negative impact on the environment. Hence, reclaim of wastes has attracted more and more attentions nowadays. Weak waste soils from construction sites or dredging sites can be considered as alternative raw materials for embankment filling after stabilization. The stabilized soil has become one of the new environment-friendly materials which is economic and of good engineering stability to meet the requirement of pavement construction. The primary objective of this project was to investigate the mechanical properties of stabilized soils for pavement applications. Three types of soils were used in this study. One was a fine soil (silty clay) and the other two were dewatered drilling slurries. By conducting a series of tests, the mechanical properties including unconfined compressive strength, California bearing ratio (CBR), triaxial shear strength, splitting tensile strength and stiffness modulus were investigated. The effects of stabilizer content, moisture content, curing and sampling preparation method and wetting-drying cycles on the mechanical properties of the stabilized soil were studied in a comprehensive manner. From a series of quantitative analyses and grey-correlation analyses, it was found that, among all stabilizers used in this study, cement is the most effective for improving the strength of the stabilized soil. Meanwhile, the moisture content has a significant effect on the strength. On the wet-side of the optimum moisture content, the strength of stabilized soil is decreased when the moisture content is raised. With the increase of the wetting-drying cycles, the strength increases to a peak value and then decreases, which is attributed to a combined effect of the change of the moisture when drying and the change of the internal structure due to the wetting-drying cycles. Numerical analyses were also conducted considering a pavement structure with a stabilized soil embankment laying on a layered soft subsoil. Settlement of the subsoil was predicted after a multi-stage construction and consolidation. Stress distribution in the embankment was obtained and the results show that the strength of the stabilized soil meets the requirement of the pavement structure. Finally, some engineering implications were concluded to guide practical pavement constructions.